Neutrophil-related immune-inflammatory biomarkers influence the early progression of medial medullary infarction - Li, Li-Min; Cai, Hao (Frontiers in Neurology, 2025)
BackgroundMedial medullary infarction (MMI) is a rare type of posterior circulation stroke for which accurate prognostication remains a challenge because of the limited predictive ability of the current models. Blood-derived biomarkers may provide valuable insights that extend beyond established prognostic factors. The aim of this study was to identify rapid and accessible biomarkers for predicting the early progression of MMI.MethodsSeventy patients with MMI and 83 sex- and age-matched healthy controls (HCs) were recruited for this study. Among them, 20 patients were allocated to the early progression cohort, and 50 patients were assigned to the nonprogression cohort. The laboratory blood indices were subsequently compared across these different cohorts. Receiver operating characteristic (ROC) curves were used to evaluate the predictive values of blood-derived indicators.ResultsThe white blood cell (WBC) count, neutrophil count, monocyte count, low-density lipoprotein cholesterol (LDL-C) level, total cholesterol (TC) concentration, WBC-to-high-density lipoprotein cholesterol (HDL-C) ratio (WHR), neutrophil-to-HDL-C ratio (NHR), monocyte-to-HDL-C ratio (MHR), monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were significantly greater in patients with MMI than in HCs (p < 0.05). The WBC count, neutrophil count, monocyte count, WHR, NHR, MHR, MLR, NLR and PLR were markedly higher in MMI patients with progression than in MMI patients without progression (p < 0.05). ROC curve analysis revealed that the WBC count, neutrophil count, monocyte count, MLR, NLR, PLR, NHR, and WHR were significant predictors of early progression. However, among these factors, the WBC count (AUC = 0.854, p < 0.001), neutrophil count (AUC = 0.878, p < 0.001), NLR (AUC = 0.861, p < 0.001), and NHR (AUC = 0.848, p < 0.001) had the highest levels of accuracy for predicting early progression in patients with MMI.ConclusionThe efficacy of the WBC count, neutrophil count, NLR and NHR is superior in predicting progression in patients with MMI. The current findings suggest that these indicators may serve as reliable, cost-effective, and innovative prognostic markers for MMI.